2019
DOI: 10.1080/09613218.2019.1665980
|View full text |Cite
|
Sign up to set email alerts
|

Embodied energy data implications for optimal specification of building envelopes

Abstract: Highly insulated building envelopes have become more commonplace as environmental imperatives require reduction of building carbon footprints. Whilst increased insulation levels reduce operational energy demand, the additional embodied energy investment can increase the buildings' overall environmental impact. The embodied energy consideration can determine whether, and to what extent, additional insulation is justified. The following paper investigates the impact of uncertainties of embodied energy data on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…It should be noted that the EU cost-optimal methodology focuses primarily on operational energy. Nonetheless, research studies have indicated that the embodied energy for thermal insulation materials may be higher than the operational energy they save during service life ( [52], [53], [54], [56]). The environmental impacts and the consumption of renewable and non-renewable primary energy on the embodied, transport, and operational energy for vacuum insulation materials should also be addressed, since vacuum panels may have an environmental impact greater than other insulation materials [55].…”
Section: /27mentioning
confidence: 99%
“…It should be noted that the EU cost-optimal methodology focuses primarily on operational energy. Nonetheless, research studies have indicated that the embodied energy for thermal insulation materials may be higher than the operational energy they save during service life ( [52], [53], [54], [56]). The environmental impacts and the consumption of renewable and non-renewable primary energy on the embodied, transport, and operational energy for vacuum insulation materials should also be addressed, since vacuum panels may have an environmental impact greater than other insulation materials [55].…”
Section: /27mentioning
confidence: 99%
“…total carbon (Resalati et al, 2020). Furthermore, Azari (2014) examined six environmental impacts based on envelope scenarios for a two-storey office building in Seattle, US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study emphasised the combined assessment for operational and embodied carbon of various insulation types of a typical semi-detached residential building located in the UK. The additional insulation materials played a role in increasing total carbon (Resalati et al , 2020). Furthermore, Azari (2014) examined six environmental impacts based on envelope scenarios for a two-storey office building in Seattle, US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although VIPs offer very low thermal conductivity (0.004-0.007 W/(m.K)), up to 10 times better than other conventional thermal insulation materials (such as mineral wool, PUR, EPS and XPS), their relative embodied energy (EE) investment is higher. Resalati et al (2020) demonstrated in their study that the EE of fumed-silica based VIPs (GJ/m 2 ) for a given R-value (thermal resistance measured in m 2 .K/W) can also be up to 10 times (in the most extreme cases) greater than conventional insulation materials on a cradle to gate basis (Figure 1). The core material, barrier envelope, getter and desiccant are the main parts that make up a VIP (Figure 2) (Alam et al, 2011).…”
Section: Introductionmentioning
confidence: 96%